The historicization of nostalgia, locality and quotidianity: on the changes in Lim Kim Chern’s gastronomic writing - Teoh, Hooi See; Tsai, Yiing Ing (Taylor & Francis, 2018)
This article seeks to shed light on Lim Kim Chern’s gastronomic writing, by ensconcing this individual case in the context of Modern Chinese Prose as an enduring literary tradition, in order to elicit the attribute of locality with diasporic discourse in quotidian life, that distinguishes it as part of a work in Malaysian Chinese Literature than the others. We will further this quest, by comparing the gastronomic writing of Lim before and after the changes in his literary pursuit in gastronomic writing, namely, by the comparison of the literary hierarchy of high-brow literature and the sub-genre of literature that post-positions the literariness, in order to examine whether or not it is a revelation, or even a harbinger of the fate of Malaysian Chinese Literature being minor literature.